2016
DOI: 10.1080/01652176.2016.1252073
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Leishmania (L.) infantum in stray dogs by molecular techniques with sensitive species-specific primers

Abstract: Background: Canine visceral leishmaniasis (CVL) is a worldwide parasitic zoonosis caused by Leishmania (Leishmania) infantum around the world. Canids are the definitive hosts and sand flies the intermediate hosts.Objective: To test the hypothesis that a new species-specific primers (Lch14:Lch15, targeting a multiple alignment for L. infantum kDNA minicircle) is an efficient diagnostic tool for L. infantum. Methods: The presence of L. infantum DNA was assessed in blood samples of 69 stray dogs using the convent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…Among them, the mini exon/spliced leader gene (Azmi, Nasereddin, Ereqat, Schönian, & Abdeen, 2010;Marfurt, Niederwieser, Makia, Beck, & Felger, 2003), the hsp70 gene (Montalvo, Fraga, Maes, Dujardin, & Van Der Auwera, 2012), the ribosomal internal transcribed spacer (ITS1-2) regions (de Almeida et al, 2011;Del Río et al, 2014;Schönian et al, 2003) and the kinetoplast, mitochondrial DNA (kDNA) (Millán et al, 2011;Souza Castro et al, 2018) have enough sequence polymorphisms to allow sensitive detection of genetic variability within Leishmania species (Akhoundi et al, 2017). Their high copy number and the presence of variable and conserved DNA regions make them ideal for pathogen detection (high sensitivity) and typing (variability studies) (de Almeida et al, 2011;Schönian et al, 2003;Silva, Richini-Pereira, Kikuti, Marson, & Langoni, 2017). Intraspecific variability was recorded in the internal transcribed spacer 2 (ITS2) sequence of L. infantum from humans, dogs and wildlife from Spain (Del Río et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the mini exon/spliced leader gene (Azmi, Nasereddin, Ereqat, Schönian, & Abdeen, 2010;Marfurt, Niederwieser, Makia, Beck, & Felger, 2003), the hsp70 gene (Montalvo, Fraga, Maes, Dujardin, & Van Der Auwera, 2012), the ribosomal internal transcribed spacer (ITS1-2) regions (de Almeida et al, 2011;Del Río et al, 2014;Schönian et al, 2003) and the kinetoplast, mitochondrial DNA (kDNA) (Millán et al, 2011;Souza Castro et al, 2018) have enough sequence polymorphisms to allow sensitive detection of genetic variability within Leishmania species (Akhoundi et al, 2017). Their high copy number and the presence of variable and conserved DNA regions make them ideal for pathogen detection (high sensitivity) and typing (variability studies) (de Almeida et al, 2011;Schönian et al, 2003;Silva, Richini-Pereira, Kikuti, Marson, & Langoni, 2017). Intraspecific variability was recorded in the internal transcribed spacer 2 (ITS2) sequence of L. infantum from humans, dogs and wildlife from Spain (Del Río et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In this way, we concluded that it was not feasible to perform screening with nonspecific primers for the diagnosis of Leishmania infection in equines, since not all positive animals were infected by the genus Leishmania. The specificity of these PCR primers was tested by their inability to amplify DNA from pathogens such as T. cruzi, E. canis, B. canis, and T. gondii (Almeida et al, 2013;Le Fichoux et al, 1999;R. C. Silva et al, 2017;Solcà et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Thermal cycling conditions followed those of El Tai et al (2000) [28] and Silva et al [29]. The amplified products were identified by 1.5% agarose gel electrophoresis containing 1.0 μL/10 mL of SYBR safe DNA gel stain (Invitrogen, Life Technologies, USA).…”
Section: Methodsmentioning
confidence: 99%